2023
DOI: 10.1029/2022ja031163
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Electron Precipitation Directly Driven by Poloidal ULF Waves

Abstract: The loss of energetic electrons in the radiation belts, an important process of the magnetospheric dynamics, is attributed to two mechanisms. The first mechanism is magnetopause shadowing, which occurs when the electron drift paths intersect the magnetopause (Hudson et al., 2014;Shprits et al., 2006;Ukhorskiy et al., 2006). The other is the precipitation of energetic electrons into the atmosphere, which can be driven effectively by resonant wave-particle interactions (W. Li et al., 2007;Millan & Thorne, 2007;R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 83 publications
(117 reference statements)
0
3
0
Order By: Relevance
“…It has also been shown that the poloidal‐mode waves can drive the electron precipitation within a wide energy range, although the Yin et al. (2023) study mainly focuses on more energetic electrons. It is needed for future works to study the relative roles of the FLR‐associated azimuthal and parallel electric fields in the electron precipitation driven by poloidal‐mode ULF waves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that the poloidal‐mode waves can drive the electron precipitation within a wide energy range, although the Yin et al. (2023) study mainly focuses on more energetic electrons. It is needed for future works to study the relative roles of the FLR‐associated azimuthal and parallel electric fields in the electron precipitation driven by poloidal‐mode ULF waves.…”
Section: Discussionmentioning
confidence: 99%
“…During this event, however, the amplitude of the ground‐based magnetic field pulsations in the east‐west direction are larger than those in the north‐south direction, which indicates the dominance of poloidal‐mode waves. Since the direction of the poloidal‐mode wave‐carried electric field coincides with the electron drift motion, it has been proposed that the azimuthal electric field and its induced acceleration could play a role in the electron precipitation (Yin et al., 2023). It has also been shown that the poloidal‐mode waves can drive the electron precipitation within a wide energy range, although the Yin et al.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, ULF waves can modulate the emission of lower‐band chorus waves and electrostatic electron cyclotron harmonic waves, periodically scattering energetic electrons into the loss cone, thereby giving rise to pulsating auroras (e.g., Li et al., 2023; Motoba et al., 2019; Motoba et al., 2021). ULF waves can also induce direct particle precipitation by altering the size of the loss cone (Rae et al., 2018) or the altitude of the mirror point (Yin, Zhou, Li, et al., 2023). Nonetheless, there is limited research on how ULF waves affect the formation of spatial periodic auroral structures.…”
Section: Introductionmentioning
confidence: 99%